Health Status of Elderly in Region 17 - Siripuban, Linda; Kaewpinit, Supanee (Journal of Health Science of Thailand, 2018)
The objective of this descriptive research was to study health status of 500 samples of the elderly in region 17 chosen through a multi-stage sampling. Data collection was conducted using questionnaires, interview and physical examination between July and August 2009. Data was analyzed by employing descriptive statistics: percentage and frequency. It was found that 68.6 percent of the sample group was female, early old age (60 - 69 years) 57.2 percent, medium-old (70 - 79 years) 33.2 percent and advanced age (80 and over) 9.6 percent. Most of them were graduated from primary school, married (49.6%); full ADL, self-assessment showed their health status at a moderate level (56.4%), hypertension (45.2%), cognitive impairment (6.2%), malnutrition (5.4%), and severe depression (2.2%). The findings suggested that health surveillance among elderly should be systematically conducted, so as to improve their quality of life.